2011
DOI: 10.1111/j.1463-5224.2010.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival bacterial and fungal flora in healthy horses in the UK

Abstract: The microbial species isolated are comparable with studies performed in other countries, although the frequency of Acinetobacter isolation was higher which may reflect a geographic difference. The topical antimicrobials gentamicin and chloramphenicol are appropriate first line antimicrobials for empirical treatment of corneal ulcers in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(124 citation statements)
references
References 17 publications
11
102
3
8
Order By: Relevance
“…Such discrepancy has been attributed to the ambient temperature and management to which the animal is subjected (PISANI et al, 1997;JOHNS et al, 2011); although, some authors have not identified any significant difference in the number or types of microorganisms isolated during different seasons of the year (ANDREW et al, 2003). Of the 200 samples collected in the present study, 131 (65.5%) showed bacterial growth (Table 1).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Such discrepancy has been attributed to the ambient temperature and management to which the animal is subjected (PISANI et al, 1997;JOHNS et al, 2011); although, some authors have not identified any significant difference in the number or types of microorganisms isolated during different seasons of the year (ANDREW et al, 2003). Of the 200 samples collected in the present study, 131 (65.5%) showed bacterial growth (Table 1).…”
Section: Resultsmentioning
confidence: 89%
“…Similar findings were respectively reported by SANTOS et al (2009) andFOTI et al (2013) in studies with dogs and horses with healthy eyes. JOHNS et al (2011), meanwhile, reported the genus Acinetobacter as the most representative for the group of gram-negative bacteria, and did not identify Proteus mirabilis in their study. In accordance with these authors, we reported a high prevalence of Acinetobacter sp., probably due to the contamination of the environment around the horse's skin, besides being considered part of the normal microflora of the human skin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations